Science’s teaching in the elementary level - Tacca Huamán, Daniel Rubén (2014)
In the last years, Science development has allowed people to change their attitude towards their own worldview. Thus, the importance of Natural Sciences was finally understood as well as its fundamental role in the development of investigative skills. Teaching Natural Sciences in the areas of Biology, Chemistry, and Physics must be in agreement with student’s developmental process and mental maturity. This is so, that in Kindergarten it is not expected that children seek for an explanation of facts and events that occur worldwide. Instead, they should be expected to know them and able to describe them. In Primary school, there is a slow and gradual approach from ideas describing the world to ideas that begin to build knowledge, therefore, those ideas will be the basis for making first explanations. Finally, at High School, a critical and reflective thinking is developed in such a way that provides students the necessary tools to operate in reality, get to know it and transform it.